Anlisis QoS Open IMS Core berbasis Network Function Virtualization pada Protokol TCP - Khoirunnidzom, Nizam; Pranindito, Dadiek; Ikhwan, Syariful (Politeknik Harapan Bersama, 2019)
IP Multimedia Subsystem (IMS) is an NGN technology to convergence support of wireline and wireless networks with QoS guarantees. Therefore IMS is widely used by telecommunications operators. Increasing customers make operators overwhelmed by having to replace or add new devices to increase IMS capacity, which is less profitable for operators on the operational costs. The concept of Network Function Virtualization (NFV) is solve the problem. The concept changed of hardware-dedicated to software-dedicated in a virtual environment allows the NFV to be more flexible in increasing device capacity and can reduce dependence on hardware purchases. In this research IMS implemented using Open IMS Core and NFV infrastructure software using OpenStack. analysis based on QoS file transfer services and web servers by measuring parameters throughput, delay, jitter, and packet loss. Based on the measurement of QoS parameters obtained by traffic load of 0 Mbps, 10 Mbps, 20 Mbps, 30Mbps. The throughput average values on file transfer service are 0.2906 Mbit / s and 16.4366 Mbit / s on web server services. The delay average value on file transfer service is 25.5077 ms and 0.7708 ms on the web server service. The resulting jitter value is less than 1 ms. Percentage of packet loss is less than 1%.